Sodiation‐based in‐source collision for profiling of pyranocoumarins in Radix Peucedani (Qianhu): utility of sodium adducts' stability with in‐source collision. (8th February 2017) - Yang, W.; Li, Y.; Kang, C.; Zhao, H.; Xiang, L.; Li, C.; Wang, Q.
Abstract : Full scan mode of liquid chromatography‐mass spectrometry equipped with an electrospray ionization source offers a chance on global detection of complicated components; however, the scan mode carries significant challenges in rapidly capturing information of analysts. Sodiation‐based in‐source collision was proposed here, as a technique for rapid detecting untargeted analytes in full scan analysis, which was based on the stability of sodium adducts and the nonselectivity of in‐source collision. Then the technique was applied to profile of angular‐type pyranocoumarins (APs) in Radix Peucedani, with full scan analysis performed at two specific in‐source collision energy: a high energy 50 V that is tolerated by the sodium adducts of APs, and a low energy 10 V, at which abundant adducts were offered. The spectra list of two average mass spectra was exported, and stable ions were selected based on the intensity ratio of standards at the two collision energy. Then 27 plausible [M + Na] + m/z values of APs were acquired after filtering the fragment ion and isotope ions and validating with [M + NH4 ] + . Eighty‐two APs finally were tentatively identified based on their accurate spectral data of MS n, fragmentation rules, and elution order regardless of their absolute configuration, which included 25 reported APs from Peucedanum praeruptorum Dunn. The technique provided a novel application of sodium adduct in qualitative analysis. And it was valuable for rapidly capturing information of analytes in full scan analysis, not only for APs but also for other compounds that could form sodium adducts. Copyright © 2017 John Wiley & Sons, Ltd.